2007
DOI: 10.1007/s12029-007-9007-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of KW-2189, a DNA Minor Groove-Binding Agent, in Patients with Hepatocellular Carcinoma: A North Central Cancer Treatment Group (NCCTG) Phase II Clinical Trial

Abstract: KW-2189 showed evidence of anti-tumor activity in HCC. However, because of significant and prolonged hematologic toxicity, when given as a single dose every 6 weeks, further development of this drug in HCC is not possible. Further exploration of DNA minor groove-binding agents in the treatment of HCC appears warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Quantum mechanical calculations revealed that these contacts include catalytic charge-dipole and CH-π interactions that preferentially stabilize the transition state. We show in vitro and in vivo how this unique means of recognition and catalysis enables AlkD to repair large adducts formed by yatakemycin, a member of the duocarmycin family of antimicrobial natural products exploited in bacterial warfare and chemotherapeutic trials 6,7 . Bulky adducts of this or any type are not excised by DNA glycosylases that utilize a traditional base-flipping mechanism 5 .…”
mentioning
confidence: 98%
“…Quantum mechanical calculations revealed that these contacts include catalytic charge-dipole and CH-π interactions that preferentially stabilize the transition state. We show in vitro and in vivo how this unique means of recognition and catalysis enables AlkD to repair large adducts formed by yatakemycin, a member of the duocarmycin family of antimicrobial natural products exploited in bacterial warfare and chemotherapeutic trials 6,7 . Bulky adducts of this or any type are not excised by DNA glycosylases that utilize a traditional base-flipping mechanism 5 .…”
mentioning
confidence: 98%
“…However, a more recent Phase II trial showed some evidence of antitumour activity in patients with hepatocellular carcinoma and further studies against this disease are warranted [114]. …”
mentioning
confidence: 99%
“…Different analogues progressed into clinical phase I and II, but their hematologic toxicity led to severe side effects and termination of treatment 1c. 2 One promising strategy to overcome these limiting effects is the antibody‐directed enzyme prodrug therapy (ADEPT), which combines the use of “nontoxic” prodrugs and antibody‐conjugated enzymes that control drug release 3. Excellent results were achieved with prodrug 3 (Scheme ), which contains a seco‐CBI4 analogue of duocarmycin (CBI=cyclopropabenzindole) connected to a galactose moiety 5.…”
Section: Methodsmentioning
confidence: 99%